Efektivitas Komunikasi Organisasi Dalam Meningkatkan Kinerja Karyawan PT. Perkebunan Nusantara IV Ajamu Kabupaten Labuhanbatu - Gustiana, Lisa; Haris, Abdul; Walhidayat, Taufik (Universitas Medan Area, 2024)
The effectiveness of organizational communication at PT. Nusantara IV Ajamu Plantation, Labuhanbatu Regency is the key to the company's success in achieving its business goals. This study aims to understand the role of organizational communication in improving employee performance and identify supporting and inhibiting factors. The research method used is qualitative with a descriptive approach, using observation, interviews, and documentation as data collection techniques. The results showed that effective organizational communication occurs through various forms such as verbal, horizontal, and vertical. Supporting factors include a corporate culture and an environment that supports collaboration between superiors and subordinates. However, technical obstacles such as network problems and adaptation to the online work system during the COVID-19 pandemic are the main inhibiting factors in improving employee performance. Keywords: effectiveness, organizational communication, employee performance